Energetic Competencies in Electronic Engineering Education A Sustainable Social Commitment - Forero-GarcÃa, Edwin; Paola Castañeda, Diana; Corredor-Cely, Jorge; Luis Paternina, José (Journal of Engineering Education Transformations, 2022)
In this article, we present electronic engineering as a discipline called to propose solutions to achieve energy sustainability. This field of knowledge has been supported to accelerate energy consumption with technological contributions to allow the comforts of the modern world . Consequently, electronics has influenced advances such as transport systems, innovations in means of communication, automation of production, domotics, and all direct impacts in the economic, political, and educational sectors. In the same way, it is then possible for electronic technology to promote development both in generating energy resources in a sustainable way and by reducing micro and macro consumption. Up to now, engineering education has promoted scientific and technological training to provide solutions that address the different needs of society, including alternative energy transformation systems. However, it has not been concerned with including in each lesson an awareness of energy efficiency and developing solutions based on sustainable use of energy. Up to now, engineering education has promoted scientific and technological training to provide solutions that address the different needs of society, including alternative energy transformation systems. Nevertheless, it has not been concerned with including in each lesson an awareness of energy efficiency and developing solutions based on sustainable use of energy. As a resource of help, we propose in this work the inclusion of "energy competences" in each topic and learning space from an Electronic Engineering program. The work presented shows that it is possible to include energy competences in electronic engineering curricula as a part of an educational sustainable social commitment.